CYCLIC VOLTAMMETRY of H2SeO3 USING COPPER AMALGAM ELECTRODE LEADING TO ANALYSIS OF SELENIUM BY DIFFERENTIAL PULSE VOLTAMMETRY - Dara, Fitri
Selenium is an essential trace element for human. Besides the range of concentration, the beneficial and toxic effects of selenium also depend on its chemical form. In natural environment and in the cell of some living organisms, selenium presents both in organic and inorganic forms. Based on some studies, the inorganic species are more toxic than organics ones, especially selenite. The concentration of selenium in natural water system is very low, with dominance of inorganic (selenite and selenate) species.